Pengendalian Hayati Afid pada Tanaman Cabai Merah dengan Menochilus sexmaculatus - Dahlia Simanjuntak; F. X. Wagiman; Laksminiwati Prabaningrum (Universitas Gadjah Mada, 2011)
A field trial on biological control of aphids (Homoptera: Aphididae) with Menochilus sexmaculatus (Coleoptera: Coccinellidae) was conducted at red chilli field in Sleman, Yogyakarta, in the planting season of 2010. Second instar was released at rate of 1 larva/250 aphids. The number of predator per plant varied depending on aphid-population density. The effectiveness of the predator was compared with application of sihalotrin 25 g/l at concentration rate of 2 cc/l as much as 500 l/ha. The results showed that effectiveness of the predator application was equal with the insecticide application. Percobaan lapangan pengendalian hayati Aphis spp. (Homoptera: Aphididae) dengan Menochilus sexmaculatus (Coleoptera: Coccinellidae) dilakukan di lahan cabai merah di daerah Sleman, Yogyakarta, pada musim tanam tahun 2010. Satu ekor larva instar II dilepas pada populasi 250 ekor afid. Banyaknya predator per tanaman bervariasi tergantung kepadatan populasi afid. Keefektifan aplikasi predator dibandingkan dengan perlakuan sihalotrin 25 g/l, konsentrasi 2 cc/l sebanyak 500 l/ha. Hasil kajian menunjukkan bahwa keefektifan aplikasi predator setara dengan aplikasi insektisida